Respostas

A melhor resposta!
2014-07-04T20:56:18-03:00
a)2 x + 6 = x + 18,                                                b) 5 x – 3 = 2x + 9
   2x-x=18-6                                                               5x-2x=9+3
     
 x=12                                                                      3x=12
     
                                                                                x=12/3
                                                                                      x=4


c)3 (2x-3) + 2 (x + 1) = 3x + 18                             d) 2 (x + 1) – 3 (2x – 5) = 6x – 3
    6x-9+2x+2=3x+18                                                  2x+2-6x+15=6x-3
    6x+2x-3x=18+9                                                       4x-6x=-3-2                         
      12x=27                                                                      -2x=-5
       x=27/12                                                                       x=5/2
       x=2,25                                                                          x=2,5

1 5 1